Heritable, population-wide damage to cells as the driving force of neoplastic transformation. - Rubin, H (1995)
Prolonged incubation of NIH 3T3 cells under the growth constraint of confluence results in the death of some cells in a manner suggestive of apoptosis. Successive rounds of prolonged incubation at confluence of the surviving cells produce increasing neoplastic transformation in the form of increments in saturation density and transformed focus formation. Cells from the postconfluent cultures are given a recovery period of various lengths to remove the direct inhibitory effect of confluence before their growth properties are studied. It is found that with each round of confluence the exponential growth rate of the cells at low densities gets lower and the size of isolated colonies of the same cells shows a similar progressive reduction. The decreased growth rate of cells from the third round of confluence persists for > 60 generations of growth at low density. The proportion of colonies containing giant cells is much higher after a 2-day recovery from confluence than after a 7-day recovery. Retardation of growth at low density and increased saturation density appear to be two sides of the same coin: both occur in the entire population of cells and precede the formation of transformed foci. We propose that the slowdown in growth and the formation of giant cells result from heritable damage to the cells, which in turn drives their transformation. Similar results have been reported for the survivors of x-irradiation and of treatment with chemical carcinogens and are associated with the aging process in animals. We suggest that these changes result from free radical damage to membrane lipids with particular damage to lysosomes. Proteases and nucleases would then be released to progressively modify the growth behavior and genetic stability of the cells toward autonomous proliferation.